Targeted Endoradiotherapy with Lu2O3-iPSMA/-iFAP Nanoparticles Activated by Neutron Irradiation: Preclinical Evaluation and First Patient Image - Myrna Luna-Gutiérrez; Blanca Ocampo-García; Nallely Jiménez-Mancilla; Alejandra Ancira-Cortez; Diana Trujillo-Benítez; Tania Hernández-Jiménez; Gerardo Ramírez-Nava; Rodrigo Hernández-Ramírez; Clara Santos-Cuevas; Guillermina Ferro-Flores (MDPI AG, 2022)
Prostate-specific membrane antigen (PSMA) is expressed in a variety of cancer cells, while the fibroblast activation protein (FAP) is expressed in the microenvironment of tumors. Previously, we reported the ability of iPSMA and iFAP ligands to specifically target PSMA and FAP proteins, as well as the preparation of stable 177Lu2O3 nanoparticles (<100 nm) functionalized with target-specific peptides. This research aimed to evaluate the dosimetry and therapeutic response of Lu2O3-iPSMA and Lu2O3-iFAP nanoparticles activated by neutron irradiation to demonstrate their potential for theranostic applications in nuclear medicine. The biokinetic behavior, radiation absorbed dose, and metabolic activity ([18F]FDG/micro-PET, SUV) in preclinical tumor tissues (athymic mice), following treatment with 177Lu2O3-iPSMA, 177Lu2O3-iFAP or 177Lu2O3 nanoparticles, were assessed. One patient with multiple colorectal liver metastases (PSMA-positive) received 177Lu2O3-iPSMA under a "compassionate use" protocol. Results indicated no significant difference (p < 0.05) between 177Lu2O3-iPSMA and 177Lu2O3-iFAP, regarding tumor radiation absorbed doses (105 ± 14 Gy, 99 ± 12 Gy and 58 ± 7 Gy for 177Lu2O3-iPSMA, 177Lu2O3-iFAP, and 177Lu2O3, respectively) and tumor metabolic activity (SUV of 0.421 ± 0.092, 0.375 ± 0.104 and 1.821 ± 0.891 for 177Lu2O3-iPSMA, 177Lu2O3-iFAP, and 177Lu2O3, respectively) in mice after treatment, which correlated with the observed therapeutic response. 177Lu2O3-iPSMA and 177Lu2O3-iFAP significantly inhibited tumor progression, due to the prolonged tumor retention and a combination of 177Lu radiotherapy and iPSMA or iFAP molecular recognition. There were negligible uptake values in non-target tissues and no evidence of liver and renal toxicity. The doses received by the patient's liver metastases (42-210 Gy) demonstrated the potential of 177Lu2O3-iPSMA for treating colorectal liver metastases.